Improved Endurance of Ferroelectric HfxZr1–xO2 Integrated on InAs Using Millisecond Annealing (Adv. Mater. Interfaces 27/2022). Issue 27 (23rd September 2022) - Athle, Robin; Blom, Theodor; Irish, Austin; Persson, Anton E. O.; Wernersson, Lars‐Erik; Timm, Rainer; Borg, Mattias
Abstract : Improved Endurance of Ferroelectric Hf x Zr1‐ x O2 Integrated on InAs The benefits of using a milliseconds flash lamp annealer to crystallize Hf x Zr1‐ x O2 into the ferroelectric orthorhombic crystal phase are highlighted in article number 2201038 by Robin Athle, Mattias Borg, and co‐workers. By annealing 1000x faster than traditional rapid thermal processing, integration of ferroelectric Hf x Zr1‐ x O2 on thermally sensitive substrates such as III‐V semiconductors can be achieved. This approach allows for exceptional material integration in emerging memory and neuromorphic applications.